Systemic effects of Optos versus indirect ophthalmoscopy for retinopathy of prematurity screening - Fung, Timothy H.M.; Abramson, Janine; Ojha, Shalini; Holden, Roger (Elsevier, 2018)
Many regions of the world have a relative shortage of ophthalmologists trained and willing to screen for retinopathy of prematurity (ROP).1 As a result, many regions have turned to retinal imaging and telemedicine.2 Optos ultrawide-field retinal imaging (Optos PLC, Dunfermline, UK) has recently been used as a screening tool for ROP.3,4 However, there are no data available regarding the systemic effects or stress induced by a ROP screening examination with the Optos. In this prospective, randomized, crossover study, we determined the effects of Optos ultrawide-field screening examination on cardiorespiratory indices, as a measure of stress, and compared the stress response with that of conventional binocular indirect ophthalmoscopy (BIO) examination.